Global dimensions of public administration and governance : a comparative voyage - Raadschelders, J. C. N.; Vigoda-Gadot, Eran, 1966-; Kisner, Mirit (america: Jossey Bass, 2015)
A comparative, interdisciplinary examination of the mechanisms behind public administration Global Dimensions of Public Administration and Governance is a comprehensive, comparative text on the structure and function of governments around the world. Written by two of the field's leading public administration scholars, this book provides an interdisciplinary perspective and a global, historical, and theoretical examination of the management and governance of the modern state. Readers learn how territory, bureaucracy, and political systems influence policy and reform in over thirty countries, and how these mechanisms affect the everyday lives of citizens. This comparative approach features rich examples of how policy is shaped by culture, and how modern policy principles are filtered to fit a country's needs and expectations. Chapters conclude with comparative analyses that help readers better-understand the role and position of government in the contemporary world, both in democratic societies and less-than-democratic environments. Governance doesn't happen in a vacuum. Those responsible for policy, regulation, and reform take cues from history, current events, and visions for the future to inform thinking on matters that can potentially affect a large number of everyday lives. This book illustrates the thought process, providing the necessary insight these important decisions require. -Understand the relationship between structure and function of government -Learn how policy is culture-dependent -Examine the political and societal contexts of reform -Discover the myriad forms of modern bureaucracy The various social sciences provide valuable information and perspectives for those involved in public administration. Those perspectives converge here to form a thorough, well-rounded, examination of the success and failure possible, and the mechanisms through which they take place. Global Dimensions of Public Administration and Governance provides a detailed, wide-ranging look at how modern governments operate, how they got this far, and where they're headed for the future. --Provided by publisher.
I. Globalization and government: Combining global and comparative perspectives upon the state of modern government -- Part 1: The origin, development, and dissemination of government: Structuring territory and organization -- 2. The roots and development of governance, government, and public administration: The envelopment of local communities in upper-local polities over time -- 3. Structuring governance and government: The layered territorial and bureaucratic organization of the world -- 4. State making, nation building, and citizenship -- 5. Political-administrative systems and multilevel government -- 6. Bureaucratic organization and culture -- 7. Organization, management, and policy: Comparing the competencies of government and public administration -- 8. Bureaucracy as personnel system and political-administrative relations -- Part 2. Managing policies: Continuity, change, and diversity -- 9. Traditional government activities I: National defense, police, law and order -- 10. Traditional government activities II: Economy, finance, and taxation systems -- 11. Social-economic services: Energy management, planning and zoning, industry and trade -- 12. Welfare services and policies: Health care, education, and social services -- 13. A vision for comparative theory and practice: Horizons of the comparative voyage -- Appendix 1: Structural similarities - cultural differences: The need for and development of comparative government studies -- Appendix 2: Motives, types and theories, methods for, and challenges of comparative perspectives.
Includes bibliographical references (pages 475-524) and index.
Rasal
Keywords: Public administration; Globalization -- Social aspects; Globalization -- Political aspects; Globalization -- Political aspects; Globalization -- Social aspects; Public administration